2011
DOI: 10.1186/1471-2229-11-18
|View full text |Cite
|
Sign up to set email alerts
|

Identification of rhizome-specific genes by genome-wide differential expression Analysis in Oryza longistaminata

Abstract: BackgroundRhizomatousness is a key component of perenniality of many grasses that contribute to competitiveness and invasiveness of many noxious grass weeds, but can potentially be used to develop perennial cereal crops for sustainable farmers in hilly areas of tropical Asia. Oryza longistaminata, a perennial wild rice with strong rhizomes, has been used as the model species for genetic and molecular dissection of rhizome development and in breeding efforts to transfer rhizome-related traits into annual rice s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 72 publications
4
72
0
Order By: Relevance
“…Additionally, five of the unisequences corresponding to known rhizome-specific expressed genes (Hu et al 2011), comprising genes encoding betaine-aldehyde dehydrogenase (Os04g0464200), SL-TPS/P (Os05g0518600), naringenin-chalcone synthase (Os10g0472900), protein kinase domain-containing protein (Os01g0655500), and one hypothetical protein (Os07g0588800), were also colocalized to the regions of Rhz3, QRn5, QRn10, QRl1, and QRl7, respectively. The unisequences reported in this study will be a useful resource for gene discovery in O. longistaminata, especially of genes involved in rhizome formation and development.…”
Section: Ssr Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, five of the unisequences corresponding to known rhizome-specific expressed genes (Hu et al 2011), comprising genes encoding betaine-aldehyde dehydrogenase (Os04g0464200), SL-TPS/P (Os05g0518600), naringenin-chalcone synthase (Os10g0472900), protein kinase domain-containing protein (Os01g0655500), and one hypothetical protein (Os07g0588800), were also colocalized to the regions of Rhz3, QRn5, QRn10, QRl1, and QRl7, respectively. The unisequences reported in this study will be a useful resource for gene discovery in O. longistaminata, especially of genes involved in rhizome formation and development.…”
Section: Ssr Analysismentioning
confidence: 93%
“…Hu et al (2003) reported that the rhizome phenotype in O. longistaminata is controlled by two dominant complementary genes, Rhz2 and Rhz3, located on chromosomes 3 and 4. Furthermore, Hu et al (2011) identified rhizome-specific genes by genomewide differential expression analysis in O. longistaminata and suggested a complex gene regulatory network underlies rhizome development and growth.…”
Section: Introductionmentioning
confidence: 98%
“…Propagation through rhizomes makes the plant (in this case, the clone) potentially immortal. Hu et al (2011) have shown that the initiation and development of the rhizomatous trait in O. longistaminata are controlled by very complex gene networks involving several plant hormones and regulatory genes. This study has identified several quantitative trait loci, paving the way to the characterization of new genes responsible for this important trait.…”
Section: Roots Of Perennialitymentioning
confidence: 99%
“…Within this experiment, the authors found that rhizome formation was a key but not the only factor that controlled winter survival, again providing indirect evidence that many aspects of dormancy and winter-survival can be separated. More recently, other researchers have begun the task of dissecting the genes and co-expressed gene sets that might control rhizomatousness in monocots [85][86][87][88][89]. These studies have identified transcripts for several genes including transcription factors that are selectively enriched in rhizomes relative to shoots.…”
Section: Molecular Studies On Rhizomatousness In Grassesmentioning
confidence: 99%